Italy : Detailed Assessment of Compliance with the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews findings of the Detailed Assessment of Italy's Compliance with the Basel Core Principles for Effective Banking Supervision. The Italian banking system seems to exhibit a high degree of resilience to possible macroeconomic shocks, as supported by the evolution of some financial soundness indicators and by the results of various model simulations. Despite significant improvements over the last few years, the quality of banks' loan portfolios remains moderate. Cost-cutting and restructuring remain key challenges for Italian banks, with several conjunctural factors putting pressures on costs and income.